Long‐term outcome of transurethral laser ablation for recurrent non‐muscle invasive bladder cancer: An EORTC risk‐matched study - Chase Peng Yun Ng; Alexander Light; Charis Eleftheriou; Oliver Hug; Ellie Richardson; Tarra Gill‐Taylor; Altaf Shamsuddin; Hamid Abboudi; Sachin Agrawal (BJUI Compass)
Abstract Introduction Elderly and comorbid patients with non‐muscle invasive bladder cancer (NMIBC) often undergo repeated transurethral resection of bladder tumour (TURBT) under general anaesthesia. Transurethral laser ablation (TULA) is an outpatient‐based alternative with lower morbidity, cost and carbon footprint, but its long‐term efficacy is not well‐established. We report the long‐term outcomes of recurrent NMIBC treated with TULA, stratified by European Organisation for Research and Treatment of Cancer (EORTC) risk groups. Materials and Methods We conducted a single‐centre, retrospective cohort study, including all consecutive NMIBC patients treated with TULA between 2012 and 2023. The primary outcomes were recurrence‐free survival (RFS) and progression‐free survival (PFS) and secondary outcomes included cancer‐specific survival (CSS), overall survival (OS) and complications, stratified by EORTC risk groups. Data were analysed using Kaplan–Meier survival analysis and Cox regression model. Results Three hundred and nineteen patients (1186 TULAs), with a median age of 77 and median Charleson Comorbidity Index of 7, were included. Median follow up was 4.4 years. The 5‐year RFS of intermediate‐risk and high‐risk NMIBC treated with TULA were 31.8% (95%CI:25.6–39.7%) and 29.0% (95%CI: 20.1–42.0%), respectively, with no significant difference (p:0.47). The 5‐year PFS were 86.8% (95%CI: 82.1–91.7%) and 93.1% (95%CI: 85.2–100.0%), respectively. Overall, the 10‐year OS and CSS were 50.7% (95% CI: 41.8–61.5%) and 96.1% (95%CI: 93.3–98.9%), respectively. The complication rate was 4.0%. Age was the only positive predictor of recurrence. Limitations include missing data (7.9%) and single‐centre retrospective design. Conclusion TULA is a safe, minimally invasive treatment with long‐term efficacy for elderly and comorbid patients with recurrent NMIBC. Although recurrence rate at 5 years were high, progression rate, especially muscle invasion, was low and reassuring. Long‐term overall survival and cancer‐specific survival remained excellent.